Identification of therapeutic targets for chronic kidney disease through Mendelian randomization analysis of druggable genes - Run-Sen Liang; Jin-Qi Su; Xiang-Qi Wu; Qi Wang; Yong-Mei Cai; Hong-Yong Su; Ji-Xin Tang; Cui-Wei Yao (Scientific Reports)
Abstract Chronic Kidney Disease (CKD) is a multifaceted and gradually advancing condition characterized by a complex pathogenesis. The current therapeutic options for CKD remain limited in efficacy. Consequently, the identification and exploration of novel drug targets for CKD are of paramount importance. We identified cis-expression quantitative trait loci (cis-eQTLs) with potential as drug targets from the eQTLGen Consortium database to serve as the exposure. For the outcome, we utilized a genome-wide association study (GWAS) of chronic kidney disease (CKD) from the FinnGen database, which comprised a case group of 11,265 individuals and a control group of 436,208 individuals. MR analysis was employed to investigate druggable genes closely associated with CKD. Subsequently, Gene Ontology (GO) and Kyoto Encyclopedia of Genes and Genomes (KEGG) enrichment analyses were conducted to elucidate the functional roles of these significant genes. Finally, a colocalization analysis was conducted to determine the likelihood that a cis-eQTL for a druggable gene and CKD share a causal variant. The expression of 12 genes was found to be significantly associated with CKD risk, with a false discovery rate (FDR) of less than 0.05. GO and KEGG enrichment analyses indicated that these genes are primarily involved in the regulation of MAP kinase activity, regulation of protein serine/threonine kinase activity, Gap junction, Platelet activation and Oxytocin signaling pathway. The colocalization analysis results suggested that CKD and the TUBB gene may share a causal variant, with a posterior probability (PP.H4) exceeding 80% (TUBB: 97.27%). Compelling statistical evidence indicates that TUBB represents the most promising pharmacological target for the treatment of CKD. This study not only identifies potential therapeutic targets but also offers valuable insights for future drug development in the context of CKD.